Oral Rehabilitation of a Patient with Papillon Lefèvre Syndrome Using Fixed Full-Arch Hybrid Prostheses Supported by Four Axially Loaded Implants: A Case Report with Four-Year Follow-up - Kumar Sharma Pawan; Vasudevan Karthikeyan; Krishnan Murugesan; Balasubramaniam Muthukumar; Krishna Kumar Raja; Sivanesan Karthikeyan Jagdish (Tehran University of Medical Sciences, 2023)
This report details the successful prosthetic rehabilitation of a 25-year-old male patient with Papillon Lefèvre Syndrome (PLS) using an implant-supported hybrid prosthesis. Six implants were placed in the maxilla, and four were placed in the mandibular arch. All implants were inserted axially (non-tilted) and were planned to be loaded after a healing period of 6 months. One implant failed due to graft loss during the healing phase, which was removed and the remaining implants were restored with a hybrid prosthesis after 6 months, using the delayed loading protocol. The patient was followed-up for four years and all the remaining implants successfully integrated and remained fully functional during this period. The prosthesis significantly improved the functional, aesthetic, and psychological well-being of the patient. This case report is the first of its kind to use only four axially placed implants for rehabilitation of a PLS patient with a successful four-year follow-up.